Physical activity and anxiety during the COVID-19 pandemic in Tanzania: insights for public health policy in low-income contexts - Ndabi, Joyce Sifa; Simwanza, Alfa; Chukwuorji, JohnBosco C.; Tladi, Dawn; Muomah, Rosemary C.; Nwonyi, Sampson K.; Tay, Doris Akosua; Joachim, Dale; Malete, Leapetswe; Adamba, Clement; Nyawornota, Vida Korleki; Nyanynofio, Oscar Nyanyo; et al. (Frontiers in Public Health, 2024)
BackgroundThe COVID-19 pandemic heightened anxiety levels globally, disproportionately affecting low-and middle-income countries (LMICs). Physical activity (PA) has shown potential to alleviate mental health challenges, including anxiety. This study explores the relationship between PA and anxiety among Tanzanian adults during the pandemic, examining whether self-reported health status moderates this relationship and identifying demographic variations.MethodsData from 213 adults were collected using the International Physical Activity Questionnaire-Short Form (IPAQ-SF) and Generalized Anxiety Disorder-7 (GAD-7) scale. Self-reported health was also reported.ResultsVigorous physical activity was significantly associated with lower anxiety, while moderate physical activity showed weaker effects. Walking and sedentary behavior were not significantly associated with anxiety. Health status did not moderate these relationships, but subgroup analyses indicated stronger effects of vigorous physical activity among men and younger adults.ConclusionThese findings highlight the relevance of PA, particularly vigorous and moderate physical activity, in supporting mental health in LMIC contexts such as Tanzania. The findings further underscore the importance of targeted, culturally relevant physical activity interventions in LMICs to mitigate anxiety and enhance mental health resilience.